The School counselor's guide to special education - Trolley, Barbara C.; Haas, Heather S.;Patti, Danielle Campese (New York, NY : Corwin Press, 2012)
What is the school counselor's role in the special education process? How can school counselors assist students with special needs? In this comprehensive and thorough guide, the authors answer these and other questions about best practices for meeting the academic, social, and career requirements of students with disabilities. This hands-on guide clarifies the counselor's role and provides a wealth of practical strategies for navigating special education processes, using available resources, and building effective teams. The authors examine special education procedures and present interventions for preschool, school-age, and transitioning students; provide study questions for reflection; and cover topics such as: assessment and intervention, including Response to Intervention, behavioral and academic challenges associated with disabilities, collaboration with school and community personnel and medical specialists, disability categories, legal and ethical issues, individual and group counseling and special education terminology. Designed for busy school professionals, The School Counselor's Guide to Special Education is an invaluable desk reference that will help counselors respond with confidence to a wide range of student and staff needs.
1. Special education roles -- 2. Special education terminology and disability categories -- 3. Assessment and referral processes -- 4. Process and services: preschool -- 5. Process and services: school age -- 6. Process and services: college -- 7. Legal and ethical issues in special education.
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION